Blow-up Results for Viscoelastic Damped Wave Models with Friction and Nonlinear Memory - Alimerina, Omar; Kaddour, Tayeb Hadj; Hakem, Ali (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper is devoted to the study of Cauchy problem for viscoelastic damped wave models with nonlinear memory on the right-hand side. The main goal is to prove blow-up results for local (in time) energy solutions. The model that we consider is parabolic-like from the point of view of energy decay estimates of the corresponding linear Cauchy problem with a vanishing right-hand side. For this reason, we apply the test function method to prove our results.